Literature lost : social agendas and the corruption of the humanities - Ellis, John M. (John Martin), 1936- (Yale University Press, 1997)
In the span of less than a generation, university humanities departments have experienced an almost unbelievable reversal of attitudes, now attacking and undermining what had previously been considered best and most worthy in the Western tradition. John M. Ellis here scrutinizes the new regime in humanistic studies. He offers a careful, intelligent analysis that exposes the weaknesses of notions that are fashionable in humanities today. In a clear voice, with forceful logic, he speaks out against the orthodoxy that has installed race, gender, and class perspectives at the center of college humanities curricula.